Malnutrion and inadequate food consumption in hospitalized patients (Annals of Medical Research, 2022)
Aim: To evaluate the nutritional status of hospitalized patients and the consumption of foods offered in the hospital and to assess the factors affecting their food consumption.Materials and Methods: Patients over 18, who were hospitalized in the internal medicine clinics for at least 72 hours and could take oral food, were included in the study. Patients’ anthropometric measurements, demographic characteristics, and current diseases were recorded, and NRS 2002 scores were calculated. The primary endpoint was to determine the patients' food consumption in the hospital and the reasons for insufficient consumption. The secondary endpoint was the comparison of the results according to the NRS score.Results: A total of 200 patients participated in the study. The mean age was 66±18 years. NRS≥3 was in 48% of patients (n=96) and the body mass index of these patients was lower than patients with NRS
Keywords: Malnutrition; Nutritional requirement; NRS score; Nutritional support